INTERNATIONAL CRIMINAL LAW IN THE JURIDICAL SYSTEM - N. A. Zelinskaya (Russian Journal of Economics and Law)
As the crime in the recent years has been obtaining international character, there is an acute necessity for international cooperation. The article deals with various aspects of international criminal law, its interpretation and concept. The author analyzes various viewpoints on the issues of international criminal law, the treatment of this term, and gives her own opinion on the issue.